2016
DOI: 10.3341/kjo.2016.30.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal Proliferation Associated with Macular Hole and Intraoperative Perifoveal Crown Phenomenon

Abstract: PurposeTo discuss the unique morphology and origin of epiretinal proliferation associated with macular hole (EPMH) occasionally observed in full-thickness macular hole (FT-MH) or lamellar hole (LH) and to introduce the perifoveal crown phenomenon encountered when removing this unusual proliferative tissue.MethodsSixteen patients showing EPMH in spectral domain-optical coherence tomography were selected from 212 patients diagnosed with MH, LH, FT-MH, impending MH, macular pseudohole, or epiretinal membrane betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 23 publications
(62 reference statements)
2
36
0
Order By: Relevance
“…Moreover, dell’Omo et al [17] did not find baseline BCVA to be a predictor of final visual outcome. Another study identified pan-keratin, a component of RPE cells, as a component of LHEP [15]. This study hypothesized ellipsoid disruption to be a bridge for RPE cells to migrate and form LHEP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, dell’Omo et al [17] did not find baseline BCVA to be a predictor of final visual outcome. Another study identified pan-keratin, a component of RPE cells, as a component of LHEP [15]. This study hypothesized ellipsoid disruption to be a bridge for RPE cells to migrate and form LHEP.…”
Section: Discussionmentioning
confidence: 99%
“…In our LMH population, LHEP was found on the SD-OCT of 53.2% of the evaluated eyes, the highest prevalence reported so far. In previous studies, LHEP prevalence ranged between 20 and 44% [4, 11-13, 15]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations